Evaluation of the Efficiency of Physical Rehabilitation in Patients with Chronic Heart Failure and Chronic Obstructive Pulmonary Disease - Roman Evgenyevich Tokmachev, Andrey Valerievich Budnevsky, Volynkina Anna Petrovna, Olysheva Irina Alexandrovna, Tatiana Alexandrovna Chernik, Borodina Valeriia Romanovna (Pakistan Journal of Medical & Health Sciences, 2022)
Chronic heart failure (CHF) and chronic obstructive pulmonary disease (COPD) occupy one of the leading positions among the main causes of morbidity and mortality. Their comorbid course is quite common and adversely affects the prognosis of these patients. To prevent decompensation and reduce hospitalizations in this group of patients, combined methods of management are required. In addition to medical treatment, these methods include physical rehabilitation. The aim of the study: was to evaluate the effectiveness of physical rehabilitation in patients with chronic heart failure and chronic obstructive pulmonary disease using a complex of cardiorespiratory analysis, a monitoring system for patients with chronic heart failure and a 6-minute walk test. Methods: The study included 240 patients with CHF. After the initial examination, the patients were divided into groups depending on the presence or absence of COPD and the value of LVEF. Subsequently, each group was divided into a subgroup that took part in physical rehabilitation in addition to standard medical therapy and another one consist of patients that received only standard therapy. A year later exercise tolerance was re-determined using a complex of cardiorespiratory analysis, a monitoring system for patients with chronic heart failure and a 6-minute walk test (6MWT). Results and Conclusion: Conducting physical rehabilitation in patients with a comorbid course of COPD and CHF is accompanied by a significant improvement in hemodynamic parameters during exercise tests (6MWT).